Factors Associated with Menopause Age in Four Elderly at Rambah Health Center Work Area, Rokan Hulu. - Herawati, Rika (Jurnal Martenity and Neonatal, 2012)
The evidence suggests that menopausal age of women in various parts of the world is getting faster, from 51.3 years to 46.9 years. Age of menopause in Indonesia also decreased from 47 years to 45 years due to various factors. Objectives The study was conducted to determine the factors associated with menopause in four Elderly at Rambah Health Center Work Area, Rokan Hulu in 2012.